Using Design to Facilitate Self-Catheterisation for Tetraplegics with Low Hand Function, Proposing a Product Concept and Design Guidelines when Designing for People with Lower Tetraplegia - Ankarbåge, Estela M. (My University, 2024)
The master thesis project “Using Design to Facilitate Self-catheterisation for Tetraplegics with Low Hand Function. Proposing a Product Concept and Design Guidelines when Designing for People with Lower Tetraplegia”, by Estela Marie Ankarbåge, was carried out at the department of Industrial Design Engineering at Chalmers University of Technology. The project has been performed in collaboration with Wellspect HealthCare situated in Mölndal, Sweden. People with a high spinal cord injury, also called tetraplegics, are encouraged to manage activities of daily life independently to increase their self-esteem and self-confidence. Wellspect HealthCare noticed them struggling to empty their bladder by intermittent catheterisation. Although many are capable to perform the catheterisation independently, they may still need assistance to manage the various catheter products. The aim of this study was to investigate the user experience of intermittent self-catheterisation among tetraplegics with low hand function and explore if and how a product could be designed to facilitate the self-catheterisation procedure. We investigated what barriers prohibited the users from experiencing an easy intermittent catheterisation and how a product could be designed to facilitate intermittent catheterisation and increase tetraplegics’ independence. This was a qualitative study looking to discover and understand attitudes, experiences, and emotions connected to self-catheterisation. Six users, three healthcare professionals, and Wellspect employees partook in interviews, a focus group, and a workshop. The data was organised into general themes and looked at from a product pleasure perspective that provided a holistic understanding of the user experience. It was found that people with lower tetraplegia struggle with catheter products not catering to their low hand function, which makes their self-catheterisation experience filled with negative emotions. Emotions such as worry, shame, and disgust emerged before, during, and after catheterising. Users and experts alike found today’s procedure unoptimized for tetraplegics, where several product interactions required a higher hand function. Based on these insights, a conceptual product design was created to remove an important barrier to an easier self-catheterisation: attaching an extension tube to the catheter. The concept was later evaluated by a urologist who compared today’s user experience with their perspective of the user experience with the concept. Additionally, design guidelines were formulated to aid in future product development projects for tetraplegics with low hand function.
Keywords: User experience; Intermittent Self-Catheterisation; Tetraplegia; Low Hand Function; Catheter; Extension Tube; Assistive Devices; Product Pleasure; Product Development; Wellspect